The Relationship Among Attributional Style, Mentalization, and Five Anxiety Phenotypes in School-Age Children. Issue 4 (1st October 2020) - Scaini, Simona; Caputi, Marcella; Ogliari, Anna; Oppo, Annalisa
ABSTRACT: Literature has shown the importance of social cognition for emotional wellness. However, to our knowledge, few studies so far investigated the relationship between social cognition and anxiety in childhood. No study systematically examined social cognition in relation to specific domains of anxiety. By a correlational design and multivariate models, we explored in a sample of 337 children the association between five anxiety phenotypes and two social cognition domains (Mentalization/Attributional style). After controlling for depressive symptoms, we found that a good performance in the mentalization task was predicted by high levels of generalized anxiety and low levels of separation anxiety. Moreover, positive attributions for good events were predicted by low levels of social anxiety. The present findings remark the importance of rehabilitating social cognition skills in children with social/separation anxiety and depressive symptoms.